2024
DOI: 10.1146/annurev-publhealth-040617-013849
|View full text |Cite
|
Sign up to set email alerts
|

Harm Minimization and Tobacco Control: Reframing Societal Views of Nicotine Use to Rapidly Save Lives

Abstract: Inhalation of the toxic smoke produced by combusting tobacco products, primarily cigarettes, is the overwhelming cause of tobacco-related disease and death in the United States and globally. A diverse class of alternative nicotine delivery systems (ANDS) has recently been developed that do not combust tobacco and are substantially less harmful than cigarettes. ANDS have the potential to disrupt the 120-year dominance of the cigarette and challenge the field on how the tobacco pandemic could be reversed if nico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
239
0
3

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(254 citation statements)
references
References 116 publications
6
239
0
3
Order By: Relevance
“…Consistent with our participants' perceptions, a recent report from the National Academies of Sciences, Engineering, and Medicine concluded that ECIGS are far less harmful than cigarettes . A recent meta‐analysis found that ECIGS may indeed increase smoking cessation and is consistent with national survey findings, yet the National Academies report concluded that there was “insufficient evidence” from randomized controlled trials that e‐cigarettes can help people quit smoking. Of note, approximately half of our sample successfully quit smoking using ECIGS.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our participants' perceptions, a recent report from the National Academies of Sciences, Engineering, and Medicine concluded that ECIGS are far less harmful than cigarettes . A recent meta‐analysis found that ECIGS may indeed increase smoking cessation and is consistent with national survey findings, yet the National Academies report concluded that there was “insufficient evidence” from randomized controlled trials that e‐cigarettes can help people quit smoking. Of note, approximately half of our sample successfully quit smoking using ECIGS.…”
Section: Discussionmentioning
confidence: 99%
“…While health consequences of long-term ecigarette use (or vaping) are largely unknown [1][2][3][4], expert opinion regards vaping as substantially less harmful than smoking [1,5]. Mounting evidence supports this view [2,[6][7][8] and that vaping may aid smoking cessation [2,[9][10][11]. Nevertheless, concerns remain [3,12], particularly around risks of vaping introducing youth to nicotine and cigarette use [13][14][15][16], though so far regular (at least weekly) vaping by youth in the UK has been rare [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps most importantly, management of nicotine addiction with e-cigarettes only (i.e. vaping among exsmokers) is likely to be substantially less harmful than with smoking [1,2,6,7], and vaping by ex-smokers may often represent intentional replacement of cigarettes with e-cigarettes for health reasons [32]. There could also be other reasons for switching such as relative price, preference, or differences in regulation as to where the behaviour is allowed.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of defining smoking behaviour and abstinence, where e‐cigarette use falls is an issue that continues to attract debate . In our study of the real‐world effectiveness of popular smoking cessation aids , we defined our outcome as abstinence from smoking, rather than abstinence from nicotine.…”
mentioning
confidence: 99%